Description of a 2-Bit Adaptive Sigma-Delta Modulation System with Minimized Idle Tones. (6th December 2007) - Prosalentis Prosalentis, E. A. E. A.; Tombras Tombras, G. S. G. S.
Abstract : A 2-bit adaptive sigma delta modulation system that inherently eliminates the idle tones present in conventional and other adaptive sigma delta systems is described. The system incorporates both memory and look-ahead instantaneous step-size estimations and, as shown by computer simulation results apart from eliminating the unwanted idle tones despite dithering, it offers improved SNR performance and extended dynamic range.